Capacitor and manufacturing method thereof based on oxidative polymerization dispersoid
By forming a dispersion including conductive polymer and excess anion counterion in the hybrid capacitor and forming a layered structure of homogenized dispersion in the capacitor, the existing hybrid capacitors are solved in terms of stability and low leakage current, achieving lower ESR and better capacitance stability.
Patent Information
- Application Number
- CN202380065744.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-15
- Filing Date
- 2023-06-29
- Publication Date
- 2025-04-25
Smart Images

Figure BDA0005309317680000051 
Figure BDA0005309317680000091 
Figure BDA0005309317680000101
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to pending U.S. Provisional Application No. 63 / 389,509, filed on July 15, 2022, which is incorporated herein by reference. Technical Field
[0003] The present invention relates to improved capacitors, particularly hybrid capacitors. More particularly, the present invention relates to improved methods of forming hybrid capacitors including conductive polymer dispersions. Background Art
[0004] Conductive polymers are widely used in electrolytic capacitors. The most promising systems are suitable for high temperature environments and high voltages. Solid conductive polymers can be combined with liquid electrolytes, called hybrid capacitors, to ensure low leakage currents and high reliability during the operating life.
[0005] Significant progress in this field has been achieved by using conductive polymer dispersions in hybrid capacitors. A typical system is PEDOT / PSSA. In this typical system, 3,4-ethylenedioxythiophene (EDOT) is polymerized in a positively charged conductive polymer chain to form poly(3,4-ethylenedioxythiophene) (PEDOT). Poly(4-styrenesulfonic acid) (PSSA) is used as a dopant and anionic counterion. In order to obtain polymer nanoparticles that are stable in a dispersant such as water, an excess of PSSA per mole is used to obtain a negative Z potential on the particle surface. PSSA has disadvantages in terms of the conductivity of the final polymer film, because PSSA inhibits PEDOT from reaching the core in the film. However, PSSA can be dissolved in hybrid capacitors, where the conductive system is represented by both a solid electrolyte and a liquid electrolyte. PSSA in solution is aggressive to certain electrolytic capacitors, such as aluminum capacitors. Especially in high humidity environments, acids can lead to increased leakage currents, metal corrosion, and capacitor failure.
[0006] There is a continuing need for improvements in hybrid capacitors, particularly with respect to stability. An improved hybrid capacitor and method of forming the improved hybrid capacitor are provided herein. Summary of the invention
[0007] It is an object of the present invention to provide an improved hybrid capacitor and a method of forming the improved hybrid capacitor.
[0008] Another object of the present invention is to provide a hybrid capacitor comprising a conductive polymer cathode, wherein the conductive polymer cathode has a nearly neutral or positive surface charge.
[0009] Particular features of the present invention are improved capacitor performance, especially capacitance stability and lower ESR.
[0010] As will be appreciated, these and other advantages are provided in a method of forming a hybrid capacitor, the method comprising: forming a dispersion comprising a conductive polymer, a dispersant, a monomer for the conductive polymer, and a molar excess of anionic counterions per mole of conductive polymer and monomer; homogenizing the dispersion to form a homogenized dispersion; and forming a capacitor comprising a conductive layer formed from the homogenized dispersion.
[0011] Another embodiment provides a method for forming a hybrid capacitor, the method comprising: forming a dispersion comprising a conductive polymer, a dispersant, a monomer of the conductive polymer, and an anionic counterion in excess of a molar amount per mole of the conductive polymer and the monomer; homogenizing the dispersion to form a homogenized dispersion; applying the homogenized dispersion to form a layer of the homogenized dispersion on a metal oxide layer; removing the dispersant of the layer; curing the monomer to form a coating film; forming a layered structure comprising a coating film, a conductive layer, and a separator therebetween; winding the layered structure to form a working element; inserting the working element into a housing; adding a liquid electrolyte to the housing; and sealing the housing.
[0012] Another embodiment provides a hybrid capacitor. The hybrid capacitor includes a sealed housing, an anode is included in the sealed housing, a dielectric is disposed on the anode, and a conductive polymer layer is disposed on the dielectric. The surface layer of the conductive polymer layer has a sulfur concentration of at least 1% by weight. A separator and a liquid electrolyte are between the cathode and the anode.
[0013] Another embodiment provides a dispersion that includes a conductive polymer, a dispersant, a monomer for the conductive polymer, and a molar excess of anionic counterions per mole of conductive polymer and monomer. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 A schematic diagram of one embodiment of the present invention.
[0015] Figure 2 A schematic diagram of one embodiment of the present invention.
[0016] Figure 3 A schematic diagram of a conventional method of forming a capacitor.
[0017] Figure 4 A schematic diagram of one embodiment of the present invention.
[0018] Figure 5 is a diagrammatic representation of one embodiment of the present invention. DETAILED DESCRIPTION
[0019] The present invention relates to an improved hybrid capacitor and an improved method of making a hybrid capacitor. More specifically, the present invention relates to the formation of a polymer dispersion comprising a prepolymerized polymer, an excess of anionic counterions, and a monomer dispersed in a dispersant. The polymer dispersion is then used to form a solid cathode layer in a hybrid capacitor comprising a liquid electrolyte. The resulting capacitor has improved performance, particularly improvements in equivalent series resistance (ESR) and capacitance stability.
[0020] Will refer to Figure 1 An embodiment of the invention is described in which the working element is shown in a schematic partially expanded view before insertion into a container and optionally but preferably before impregnation with a liquid electrolyte. Figure 1 In the figure, the working element generally indicated at 10 includes an anode 12 and a cathode 14, with a separator 16 between the anode 12 and the cathode 14, and the separator 16 can be a conductive separator. It should be understood by those skilled in the art that the anode has a dielectric. The conductive separator has a conductive polymer coated on the separator, or the separator is impregnated with a conductive polymer, preferably the separator is saturated with a conductive polymer. Anode lead 20 and cathode lead 22 extend from the wound capacitor and ultimately form an electrical connection of the circuit. It can be understood from the description that the anode lead is in electrical contact with the anode, the cathode lead is in electrical contact with the cathode, and is electrically insulated from the anode or the anode lead. As is known in the art, connectors 24 and connectors 26 are generally used to electrically connect the anode lead to the anode and the cathode lead to the cathode. A closure 28, such as tape, prevents the working element from unwinding during handling and assembly, and thereafter, even if the closure is part of the finished capacitor, it has little effect.
[0021] Figure 2 The capacitor is shown in a schematic cross-sectional view. Figure 2 , a capacitor, generally indicated at 60, includes a working element 10 as described herein within a housing 64. The housing, which may be referred to in the art as a can, is preferably conductive and may serve as a lead or be in electrical contact with a cathode lead 66. A cathode tab 68 is in electrical contact with the housing or cathode lead. An anode tab 70 is in electrical contact with an anode lead 72. A lid 74 and a seal 76 (e.g., a gasket) seal the housing to inhibit atmospheric exchange between the interior of the housing and the surrounding atmosphere. In one embodiment, the seal is a hermetic seal.
[0022] The present invention is directed to improvements in conductive polymer layers, and more particularly, to improvements in conductive polymer layers forming a solid electrolyte on at least one of the dielectrics in the anode, cathode or separator.
[0023] Will refer to Figure 3 and Figure 4 Embodiments of the present invention are described in which a comparison of a conventional process for forming a capacitor and the process of the present invention is schematically illustrated. Figure 3 represents a conventional method for illustrating the present invention, Figure 4 This shows the method of the present invention.
[0024] exist Figure 3 In the present invention, as schematically shown in A, a preformed polymer dispersion 100 is applied to an electrolyte 102 (e.g., an anode 12). The preformed polymer dispersion includes a conductive polymer 106 and anionic counterions 108 in particle form. Although not limited to theory, it is assumed that the conductive polymer and the anionic counterions form core-shell particles, and the conductive polymer phase is at least partially encapsulated by the anionic counterions. The particles are suspended in a dispersant 110 (e.g., water). As schematically shown in B, the dispersant is removed, for example by drying, resulting in agglomerated particles dispersed on the surface of the dielectric. When cured, it is assumed that the conductive polymer phase and the anionic counterion phase coalesce to form a conductive polymer coating having a negative surface, which is due to the conductive polymer being at least partially encapsulated by the anionic counterion phase, as schematically shown in C.
[0025] exist Figure 4 In the present invention, the dispersion 120 includes a pre-made polymer dispersion, and the pre-made polymer dispersion includes as described in Figure 3 As discussed, the conductive polymer 106 and the anionic counterion 108 are in the form of particles. The dispersion of the present invention also includes a monomer 122, which is particularly insoluble in the dispersant 110, and therefore preferably includes a surfactant to stabilize the monomer, thereby forming a dispersed monomer, which is assumed to be in the form of particles, 122, as schematically shown in A. The conductive polymer, the dispersed monomer, the anionic counterion and the optional surfactant are homogenized to produce a homogenized dispersion. As schematically shown in B, when the dispersant is removed (for example by drying), the dispersed monomer is assumed to be particles that at least partially encapsulate the conductive polymer and the anionic counterion. The monomer polymerizes during the removal of the dispersant, preferably as schematically shown in C, by oxidation by oxygen due to exposure to air. Instead of Figure 3 The schematic diagram of the predominantly positively charged core and the predominantly negatively charged shell in the example Figure 4 As shown schematically, the conductive polymer layer with anionic counterions is more evenly dispersed throughout the conductive polymer layer, resulting in a neutral or positively charged surface, thereby reducing the negative potential of the surface, resulting in a decrease in the resistivity of the surface layer. Evidence for this structure is provided in scanning electron microscopy combined with energy dispersive X-ray spectroscopy (SEM EDS) and conductivity studies. Figure 3As shown, the SEM EDS of the surface formed by the conventional dispersion has a lower surface layer sulfur concentration, wherein the sulfur content is less than 0.75 wt%, while the sample of the present invention has a higher surface layer sulfur concentration, at least 1 wt%, more preferably at least 1.2 wt%, and even more preferably at least 1.4 wt%. The zeta potential analysis of the solution supports the structure of this analysis. The zeta potential of the comparative solution is about -67.7 mV, while the zeta potential of the solution of the present invention is -56.6 mV, indicating that the sample of the present invention carries more positive charge, supporting the conclusion that there are more polymers on the surface than anionic counterions.
[0026] like Figure 4 As shown, the slurry of the present invention provides a dense polymer film surface, wherein the conductive polymer is in contact with a liquid electrolyte. When a conventional slurry is used, the surface of the conductive polymer layer includes anionic counterions, which are non-conductive materials. The non-conductive layer on the surface serves as an insulating layer with a high conductive layer located inside it. A denser conductive polymer film with a minimum amount of non-conductive components on the surface has significantly higher conductivity, resulting in better electrical properties of the capacitor. Advantages of the method of the present invention include that the capacitor of the present invention has lower ESR and better stability.
[0027] Without being limited to theory, it is hypothesized that during the oxidative polymerization process, excess anionic counterions (called dopants) blend with the newly formed conductive polymer from the dispersed monomers, thereby inhibiting the dissolution of the anionic counterions in the liquid electrolyte of the finished capacitor. This is a significant improvement in hybrid capacitor technology, as dissolved anionic counterions are aggressive agents that can degrade some capacitor components. Oxidative polymerization of the dispersed monomers allows for better polymer / substrate blending, thereby preventing delamination of the polymer film, resulting in improved stability of the capacitor capacitance.
[0028] The present invention provides a method for forming a conductive polymer and capacitor that mitigates the adverse effects of excess PSSA on capacitor performance. In the present invention, a polymer dispersion is prepared in a monomer emulsion. More specifically, prepolymerized solid nanoparticles are co-dispersed with monomer in a dispersant, preferably water, wherein the monomer is in the form of micron-sized droplets or nano-sized droplets. In this case, the primary dispersant liquid is immiscible with the monomer liquid, and oxidative polymerization is preferably inhibited by eliminating the oxidant present in the slurry. The monomer droplets are preferably stabilized with a surfactant.
[0029] For the purposes of the present invention, the excess of anionic counterions (represented by PSSA) exceeds the amount required to balance the charge of the conductive polymer (represented by PEDOT) and the monomer (represented by EDOT). It is understood that after oxidative polymerization, the monomer is a polymer, or, taking representative monomers and polymers as an example, EDOT becomes PEDOT. Preferably, the weight ratio of PEDOT and EDOT / PSSA in the dispersion is at least 1:1.5 to 1:5, more preferably about 1:2 to 1:3. Preferably, the ratio of PEDOT / PSSA in the capacitor is at least 1:1.5 to 1:5, more preferably about 1:2 to 1:3. The molar ratio of PEDOT / PSSA in the dispersion is preferably at least 1:1.16 to 1:3.9, more preferably at least 1:1.5 to 1:2.3. The molar ratio of PEDOT / PSSA in the capacitor is preferably at least 1:1.16 to 1:3.9, more preferably at least 1:1.5 to 1:2.3.
[0030] The anode is preferably a metal, more preferably a valve metal selected from tantalum, aluminum, niobium, titanium, zirconium, hafnium, alloys of these elements and their conductive oxides (such as NbO). Aluminum is a particularly preferred anode material.
[0031] The dielectric is not particularly limited herein. Oxides of the anode material are particularly suitable dielectrics, but are not limited thereto, due to their widely recognized use and ease of manufacture in the art.
[0032] The preferred monomer is defined as Formula A, wherein n=1 and there is no bond between adjacent units. The preferred polythiophene is shown in Formula A:
[0033]
[0034] in:
[0035] Select R 1 and R 2 to prevent polymerization at the β-position of the ring. Most preferably, only α-position polymerization is allowed. Therefore, R 1 and R 2 is not hydrogen. More preferably, R 1 and R 2 is the α-director. Therefore, ether bonds are preferred over alkyl bonds. It is most preferred that these groups be small to avoid steric interference. For these reasons, R 1 and R 2 Taken together as -O-(CH2)2-O- is most preferred. In Formula 1, X is preferably selected from S, N or O, most preferably X is S. The subscript n for monomers is 1, and for polymers, the subscript n is 2 to a number sufficient to obtain a molecular weight of up to 100,000 g / mol. A particularly preferred conductive polymer is polymerized 3,4-polyethylenedioxythiophene (PEDOT).
[0036] R 1 and R 2 independently represent a straight or branched C1-C16 alkyl or C2-C18 alkoxyalkyl group; or unsubstituted or substituted by C1-C6 alkyl, C1-C6 alkoxy, halogen or OR 3 Substituted C3-C8 cycloalkyl, phenyl or benzyl; or R 1 and R 2 together are unsubstituted or substituted straight chain C1-C6 alkylene groups: C1-C6 alkyl, C1-C6 alkoxy, halogen, C3-C8 cycloalkyl, phenyl, benzyl, C1-C4 alkylphenyl, C1-C4 alkoxyphenyl, halophenyl, C1-C4 alkylbenzyl, C1-C4 alkoxybenzyl or halobenzyl, R 1 and R 2 Together, they form a 5-, 6-, or 7-membered heterocyclic structure containing two oxygen elements. 3 Preferably it represents hydrogen, straight-chain or branched C1-C16 alkyl or C2-C18 alkoxyalkyl, or C3-C8 cycloalkyl which is unsubstituted or substituted by C1-C6 alkyl, phenyl or benzyl.
[0037] Liquid electrolyte is a solvent, preferably with supporting salt. Any conventional solvent can be used together with exemplary solvents, and the exemplary solvents include gamma-butyrolactone, cyclopentane sulfone, ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, acetonitrile, propionitrile, dimethylformamide, diethylformamide, water, silicone oil, polyethylene glycol and mixtures thereof. Although not required, supporting salt is preferred. Exemplary supporting salts include inorganic acid ammonium salts, inorganic acid amine salts, inorganic acid alkyl-substituted amide salts, organic ammonium salts, organic acid amide salts, organic acid alkyl-substituted amide salts and derivatives thereof. Any gas absorbent or cathode electrochemical depolarizer can be used. Exemplary supported additives include nitro derivatives of organic alcohols, acids, esters, aromatic derivatives such as o-nitroanisole, m-nitroanisole, p-nitroanisole, o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenyl alcohol, m-nitrophenyl alcohol, p-nitrophenyl alcohol. Particularly preferred hybrid capacitors include up to 50 wt % of a liquid electrolyte.
[0038] Particularly preferred anionic counterions or dopants are polystyrene sulfonic acid and its derivatives, optionally in the form of random copolymers comprising groups A, B and C represented by the ratios of the following formula B:
[0039] A x B y Cz
[0040] Formula B
[0041] in:
[0042] A is polystyrene sulfonic acid or polystyrene sulfonate;
[0043] B and C each represent a polymerized unit substituted by a group selected from the following:
[0044] -carboxyl;
[0045] -C(O)OR 6 , where R 6 Selected from the following groups:
[0046] an alkyl group of 1 to 20 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, phosphate, acrylate, anhydride; and
[0047] -(CHR 7 CH2O) b -R 8 ,in:
[0048] R 7 Selected from hydrogen or alkyl of 1 to 7 carbons, preferably hydrogen or methyl; b is 1 to -CHR 7 The CH2O- groups provide integers of molecular weight up to 200,000; and
[0049] R 8 selected from the group consisting of hydrogen, silane, phosphate, acrylate, an alkyl group of 1 to 9 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride;
[0050] -C(O)-NHR 9 ,in:
[0051] R 9 is hydrogen or an alkyl group of 1 to 20 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride;
[0052] -C6H4-R 10 ,in:
[0053] R 10Selected from: hydrogen or alkyl optionally substituted with a functional group selected from: hydroxyl, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate and anhydride;
[0054] The reactive group is selected from the group consisting of hydroxyl, carboxyl, amine, epoxy, silane, imide, amide, thiol, olefin, alkyne, phosphate, azide, acrylate, anhydride; and
[0055] -(O(CHR 11 CH2O) d -R 12 ,in:
[0056] R 11 is hydrogen or an alkyl group of 1 to 7 carbon atoms, preferably hydrogen or methyl;
[0057] d is 1 to be sufficient for -CHR 11 The CH2O- group provides integers of molecular weight up to 200,000;
[0058] R 12 selected from hydrogen, alkyl groups of 1 to 9 carbons optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride;
[0059] -C6H4-OR 13 ,in:
[0060] R 13 Selected from:
[0061] hydrogen or an alkyl group optionally substituted with a reactive group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, acrylate, phosphate and anhydride;
[0062] The reactive group is selected from the group consisting of epoxy, silane, olefin, alkyne, acrylate, phosphate; and
[0063] -(CHR 14 CH2O) e -R 15 ,in:
[0064] R 14 is hydrogen or an alkyl group of 1 to 7 carbon atoms, more preferably hydrogen of a methyl group;
[0065] e is 1 to -CHR 14 The CH2O- groups provide integers of molecular weight up to 200,000; and
[0066] R15 an alkyl group of 1 to 9 carbon atoms selected from hydrogen and optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, acrylate, phosphate, and anhydride;
[0067] In one embodiment, y and z are 0; and
[0068] In another embodiment, x, y and z are taken together to form a polyanion having a molecular weight of at least 100 and not more than 500,000, y / x is from 0.01 to 100, z is from 0 to a ratio of z / x of not more than 100; more preferably, x represents 50% to 99% of the sum of x+y+z, y represents 1% to 50% of the sum of x+y+z, and z represents 0% to 49% of the sum of x+y+z; even more preferably, x represents 70% to 90% of the sum of x+y+z, y represents 10% to 30% of the sum of x+y+z, and z represents 0% to 20% of the sum of x+y+z. A particularly preferred anionic counterion is polystyrene sulfonic acid (PSSA).
[0069] Embodiment 1:
[0070] Axial hybrid capacitors with a working voltage of 63V and a capacitance of 400uF were prepared, comprising an aluminum anode with a preformed dielectric layer, an aluminum cathode, PEDOT / PSSA as a conductive polymer, and an electrolyte comprising gamma-butyrolactone (GBL), sulfolane, quaternary alkylammonium phthalate and polyethylene glycol, and a nitro compound as a stabilizer. The polymer is characterized in that the weight ratio of PEDOT / PSSA is 1:3 and the molar ratio of monomer EDOT / PSSA is about 1:2.5.
[0071] The capacitor banks of the present invention were prepared using the same conductive polymer dispersion in a 1% EDOT emulsion.
[0072] Capacitors tested at 63V and 150°C
[0073] After 250 hours of testing, the two types of capacitors were disassembled. The comparative capacitor was observed to have significant breakdown of the conductive polymer that was not observed in the examples of the present invention. Breakdown refers to the presence of dark brown residue in the area of the tab where the tab is connected to the anode lead. The residue confirms the corrosion of the metal. The residue was determined to be a sulfone group by Fourier transform infrared (FTIR) analysis.
[0074] The surfactant used to disperse the monomer in the dispersion of the present invention is preferably selected from nonionic surfactants, fluorinated surfactants, anionic surfactants, cationic surfactants and acetylenes. Particularly preferred surfactants include Triton X, FS, Zonyl FS-300, sodium dodecyl sulfate (SDS), tetraoctylammonium bromide (TOAB), 104. 420.Dynol TM 607 and Dynol TM 604.
[0075] Example 1 shows that the control polymer is aggressive to hybrid capacitors and can cause corrosion of the metal in the capacitor. The polymer of the present invention improves the compatibility of the material. This significant improvement is due to the oxidative polymerization of EDOT that occurs during the modification process. Curing is carried out at a temperature above 100°C and about 150°C, at which temperature EDOT is polymerized by the air in the layer, incorporating excess PSSA from the solid polymer.
[0076] Example 2
[0077] V-chip hybrid capacitors of 63V and 100uF were prepared, which included an aluminum anode with a preformed dielectric layer, an aluminum cathode, PEDOT / PSS as a conductive polymer, and an electrolyte including gamma-butyrolactone (GBL), sulfolane, quaternary alkylammonium phthalate and polyethylene glycol, and a nitro compound as a stabilizer. The polymer is characterized in that the weight ratio of PEDOT / PSSA is 1:3.
[0078] The capacitors of the present invention were prepared using the same conductive polymer dispersion in a 1% EDOT emulsion.
[0079] The capacitors were subjected to a durability test at 135°C and 63V (DC).
[0080] The results show significant differences in the initial ESR values and the stability of the ESR over the test time. Figure 5 , which shows the change of ESR over time.
[0081] Example 3
[0082] The conductivity of a representative inventive slurry comprising PEDOT / PSSA / EDOT was evaluated relative to a representative comparative slurry comprising PEDOT / PSSA. The results are summarized in Tables 1 and 2.
[0083] To prepare the sample, EDOT was slowly added to PEDOT / PSS (1:3) in a Silverson L5MA homogenizer. After addition, the speed was increased to 900 rpm for 15 to 20 minutes.
[0084] The experimental results show that the conductivity of the final polymer film formed from the inventive slurry in air; measured on a glass slide, 1 g of slurry dried at 90°C for 15 minutes; at 150°C for 15 minutes; has significantly higher conductivity than the comparative slurry shown in Table 2. The inventive examples show acceptable stability in pH, conductivity and viscosity, with no significant changes after 10 days of storage.
[0085] Table 1. Viscosity and pH of PEDOT / PSS (1:3) + EDOT slurries (1%, 5%, and 10%) before and after 10 days of storage (room temperature, closed container, no special gas treatment)
[0086]
[0087] Table 2. Measured parameters of PEDOT / PSS (1:3) + EDOT variants and conventional slurries
[0088]
[0089] The present invention has been described with reference to preferred embodiments but is not limited thereto. Those skilled in the art will recognize other embodiments and modifications not specifically described but within the satisfaction and limitations of the appended claims.
Claims
1. A method of forming a hybrid capacitor, comprising: forming a dispersion comprising a conductive polymer, a dispersant, a monomer for the conductive polymer, and a molar excess of anionic counterions per mole of the conductive polymer and the monomer; homogenizing the dispersion to form a homogenized dispersion; A capacitor is formed, the capacitor comprising a conductive layer formed from the homogenized dispersion. 2 . The method of forming a hybrid capacitor according to claim 1 , wherein a weight ratio of the conductive polymer and monomer to the anionic counter ion in the dispersion is 1:1.5 to 1:
5. 3 . The method of forming a hybrid capacitor according to claim 2 , wherein a weight ratio of the conductive polymer and monomer to the anionic counter ion in the dispersion is 1:2 to 1:
3. 4 . The method for forming a hybrid capacitor according to claim 1 , wherein a weight ratio of the conductive polymer to the anionic counter ion in the hybrid capacitor is 1:1.5 to 1:
5. 5 . The method of forming a hybrid capacitor according to claim 4 , wherein a weight ratio of the conductive polymer to the anionic counter ion in the hybrid capacitor is 1:2 to 1:
3.
6. The method of forming a hybrid capacitor of claim 1 comprising applying the homogenized dispersion onto a metal or metal oxide.
7. The method of forming a hybrid capacitor of claim 6, wherein the metal or metal oxide comprises a valve metal.
8. The method of forming a hybrid capacitor according to claim 6, wherein the valve metal is selected from the group consisting of tantalum, aluminum, niobium, titanium, zirconium, hafnium, alloys of these elements, and conductive oxides thereof.
9. The method of forming a hybrid capacitor of claim 8, wherein the valve metal is aluminum.
10. The method of forming a hybrid capacitor according to claim 1, wherein the monomer is defined by Formula A, wherein n=1, and there are no bonds between adjacent units; and the conductive polymer is defined by Formula A: in: X is selected from S, N or O; R 1 and R 2 independently represent a straight or branched C1-C16 alkyl or C2-C18 alkoxyalkyl group; or unsubstituted or substituted by C1-C6 alkyl, C1-C6 alkoxy, halogen or OR 3 Substituted C3-C8 cycloalkyl, phenyl or benzyl; or R 1 and R 2 together are unsubstituted or substituted straight chain C1-C6 alkylene groups: C1-C6 alkyl, C1-C6 alkoxy, halogen, C3-C8 cycloalkyl, phenyl, benzyl, C1-C4 alkylphenyl, C1-C4 alkoxyphenyl, halophenyl, C1-C4 alkylbenzyl, C1-C4 alkoxybenzyl or halobenzyl, R 1 and R 2 Together, they form a 5-, 6-, or 7-membered heterocyclic structure containing two oxygen elements. 3 Preferably it represents hydrogen, straight-chain or branched C1-C16 alkyl or C2-C18 alkoxyalkyl, or C3-C8 cycloalkyl which is unsubstituted or substituted by C1-C6 alkyl, phenyl or benzyl. The method for forming a hybrid capacitor according to claim 10 , wherein X is S.
1.
12. The method of forming a hybrid capacitor of claim 10, wherein the conductive polymer is 3,4-polyethylenedioxythiophene.
13. The method of forming a hybrid capacitor of claim 10, wherein the monomer is 3,4-ethylenedioxythiophene.
14. The method of forming a hybrid capacitor of claim 1, wherein the anionic counterion is defined as: A x B y C z in: A is polystyrene sulfonic acid or polystyrene sulfonate; B and C each represent a polymerized unit substituted by a group selected from the following: -carboxyl; -C(O)OR 6 , where R 6 Selected from the following groups: an alkyl group of 1 to 20 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, phosphate, acrylate, anhydride; and -(CHR 7 CH2O) b -R 8 ,in: R 7 is selected from hydrogen or an alkyl group of 1 to 7 carbons; b is 1 to -CHR 7 The CH2O- groups provide integers of molecular weight up to 200,000; and R 8 selected from the group consisting of hydrogen; silane; phosphate; acrylate; an alkyl group of 1 to 9 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxyl, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; -C(O)-NHR 9 ,in: R 9 is hydrogen or an alkyl group of 1 to 20 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; -C6H4-R 10 ,in: R 10 Selected from: hydrogen or alkyl optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; Active groups, the active groups are selected from: hydroxyl, carboxyl, amine, epoxy, Silanes, imides, amides, thiols, olefins, alkynes, phosphates, azides, Acrylates, anhydrides; and -(O(CHR 11 CH2O) d -R 12 ,in: R 11 is hydrogen or an alkyl group of 1 to 7 carbon atoms, preferably hydrogen or methyl; d is 1 to be sufficient for -CHR 11 The CH2O- group provides integers of molecular weight up to 200,000; R 12 selected from hydrogen, alkyl groups of 1 to 9 carbons optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; -C6H4-OR 13 ,in: R 13 Selected from: hydrogen or an alkyl group optionally substituted with a reactive group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, acrylate, phosphate and anhydride; Reactive groups, the reactive groups are selected from: epoxy, silane, olefin, alkyne, acrylate, phosphate; and -(CHR 14 CH2O) e -R 15 ,in: R 14 is hydrogen or an alkyl group of 1 to 7 carbons; e is 1 to -CHR 14 The CH2O- groups provide integers of molecular weight up to 200,000; and R 15 selected from hydrogen and alkyl groups of 1 to 9 carbons optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, acrylate, phosphate, and anhydride; and x, y and z are sufficient to form a polyanion having a molecular weight of at least 100 and not more than 500,000, wherein y / x is from 0.01 to 100; and z is from 0 to a ratio of z / x not exceeding 100.
15. The method of forming a hybrid capacitor of claim 14, wherein x represents 50% to 99% of the sum of x+y+z, y represents 1% to 50% of the sum of x+y+z, and z represents 0% to 49% of the sum of x+y+z.
16. The method of forming a hybrid capacitor of claim 15, wherein x represents 70% to 90% of the sum of x+y+z, y represents 10% to 30% of the sum of x+y+z, and z represents 0% to 20% of the sum of x+y+z.
17. The method of forming a hybrid capacitor of claim 1 wherein the anionic counterion is polystyrene sulfonic acid.
18. The method of forming a hybrid capacitor of claim 1 wherein the homogenized dispersion further comprises a surfactant.
19. The method of forming a hybrid capacitor according to claim 18, wherein the surfactant is selected from the group consisting of nonionic surfactants, fluorinated surfactants, anionic surfactants, cationic surfactants, and acetylenes.
20. The method of forming a hybrid capacitor of claim 1, wherein said forming said capacitor further comprises adding a liquid electrolyte.
21. The method of forming a hybrid capacitor according to claim 20, wherein the liquid electrolyte comprises a solvent selected from the group consisting of gamma-butyrolactone, sulfolane, ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, acetonitrile, propionitrile, dimethylformamide, diethylformamide, water, silicone oil, polyethylene glycol, and mixtures thereof.
22. The method of forming a hybrid capacitor of claim 20, wherein the liquid electrolyte comprises a salt selected from the group consisting of inorganic acid ammonium salts, inorganic acid amine salts, inorganic acid alkyl substituted amide salts, organic ammonium salts, organic acid amide salts, organic acid alkyl and substituted amide salts.
23. A method of forming a hybrid capacitor, comprising: forming a dispersion comprising a conductive polymer, a dispersant, a monomer for the conductive polymer, and a molar excess of anionic counterions per mole of the conductive polymer and the monomer; homogenizing the dispersion to form a homogenized dispersion; applying the homogenized dispersion to form a layer of the homogenized dispersion on the metal oxide layer; removing said dispersant from said layer; curing the monomer to form a coating film; forming a layered structure comprising the coating film, a conductive layer, and a separator between the coating film and the conductive layer; winding the layered structure to form a working element; inserting the working element into the housing; adding a liquid electrolyte to the housing; and The housing is sealed.
24. The method of forming a hybrid capacitor of claim 23, wherein the weight ratio of the conductive polymer and monomer to the anionic counter ion in the dispersion is 1:1.5 to 1:
5.
25. The method of forming a hybrid capacitor of claim 24, wherein the weight ratio of the conductive polymer and monomer to the anionic counter ion in the dispersion is 1:2 to 1:
3. 26 . The method of forming a hybrid capacitor according to claim 23 , wherein a weight ratio of the conductive polymer to the anionic counter ion in the hybrid capacitor is 1:1.5 to 1:
5. 27 . The method of forming a hybrid capacitor according to claim 26 , wherein a weight ratio of the conductive polymer to the anionic counter ion in the hybrid capacitor is 1:2 to 1:
3.
28. The method for forming a hybrid capacitor according to claim 23, wherein the surface layer of the coating film has a sulfur concentration of at least 1 wt%.
29. The method for forming a hybrid capacitor according to claim 28, wherein the surface layer of the coating film has a sulfur concentration of at least 1.2 wt%.
30. The method for forming a hybrid capacitor of claim 29, wherein the surface layer of the coating film has a sulfur concentration of at least 1.4 wt%.
31. The method of forming a hybrid capacitor of claim 23, wherein the metal is a valve metal.
32. The method of forming a hybrid capacitor of claim 31, wherein the valve metal is selected from the group consisting of tantalum, aluminum, niobium, titanium, zirconium, hafnium, alloys of these elements, and conductive oxides thereof.
33. The method of forming a hybrid capacitor of claim 32, wherein the valve metal is aluminum.
34. The method of forming a hybrid capacitor of claim 23, wherein the monomer is defined by Formula A, wherein n=1, and there are no bonds between adjacent units; and the conductive polymer is defined by Formula A: in: X is selected from S, N or O; R 1 and R 2 independently represent a straight or branched C1-C16 alkyl or C2-C18 alkoxyalkyl group; or unsubstituted or substituted by C1-C6 alkyl, C1-C6 alkoxy, halogen or OR 3 Substituted C3-C8 cycloalkyl, phenyl or benzyl; or R 1 and R 2 together are unsubstituted or substituted straight chain C1-C6 alkylene groups: C1-C6 alkyl, C1-C6 alkoxy, halogen, C3-C8 cycloalkyl, phenyl, benzyl, C1-C4 alkylphenyl, C1-C4 alkoxyphenyl, halophenyl, C1-C4 alkylbenzyl, C1-C4 alkoxybenzyl or halobenzyl, R 1 and R 2 Together, they form a 5-, 6-, or 7-membered heterocyclic structure containing two oxygen elements. 3 Preferably it represents hydrogen, straight-chain or branched C1-C16 alkyl or C2-C18 alkoxyalkyl, or C3-C8 cycloalkyl which is unsubstituted or substituted by C1-C6 alkyl, phenyl or benzyl.
35. The method of forming a hybrid capacitor of claim 34, wherein X is S.
36. The method for forming a hybrid capacitor of claim 34, wherein the conductive polymer is 3,4-polyethylenedioxythiophene.
37. The method for forming a hybrid capacitor of claim 34, wherein the monomer is 3,4-ethylenedioxythiophene.
38. The method of forming a hybrid capacitor of claim 23, wherein the anionic counterion is defined as: A x B y C z in: A is polystyrene sulfonic acid or polystyrene sulfonate; B and C each represent a polymerized unit substituted by a group selected from the following: -carboxyl; -C(O)OR 6 , where R 6 Selected from the following groups: an alkyl group of 1 to 20 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, phosphate, acrylate, anhydride; and -(CHR 7 CH2O) b -R 8 ,in: R 7 is selected from hydrogen or an alkyl group of 1 to 7 carbons; b is 1 to -CHR 7 The CH2O- groups provide integers of molecular weight up to 200,000; and R 8 selected from the group consisting of hydrogen; silane; phosphate; acrylate; an alkyl group of 1 to 9 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxyl, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; -C(O)-NHR 9 ,in: R 9 is hydrogen or an alkyl group of 1 to 20 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; -C6H4-R 10 ,in: R 10 Selected from: hydrogen or alkyl optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; Reactive groups, the reactive groups are selected from the group consisting of hydroxyl, carboxyl, amine, epoxy, silane, imide, amide, thiol, olefin, alkyne, phosphate, azide, acrylate, anhydride; and -(O(CHR 11 CH2O) d -R 12 ,in: R 11 is hydrogen or an alkyl group of 1 to 7 carbon atoms, preferably hydrogen or methyl; d is 1 to be sufficient for -CHR 11 The CH2O- group provides integers of molecular weight up to 200,000; R 12 selected from hydrogen, alkyl groups of 1 to 9 carbons optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; -C6H4-OR 13 ,in: R 13 Selected from: hydrogen or an alkyl group optionally substituted with a reactive group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, acrylate, phosphate and anhydride; Reactive groups, the reactive groups are selected from: epoxy, silane, olefin, alkyne, acrylate, phosphate; and -(CHR 14 CH2O) e -R 15 ,in: R 14 is hydrogen or an alkyl group of 1 to 7 carbons; e is 1 to -CHR 14 The CH2O- groups provide integers of molecular weight up to 200,000; and R 15 selected from hydrogen and alkyl groups of 1 to 9 carbons optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, acrylate, phosphate, and anhydride; and x, y and z are sufficient to form a polyanion having a molecular weight of at least 100 and not more than 500,000, wherein y / x is from 0.01 to 100; and z is from 0 to a ratio of z / x not exceeding 100.
39. The method of forming a hybrid capacitor of claim 38, wherein x represents 50% to 99% of the sum of x+y+z, y represents 1% to 50% of the sum of x+y+z, and z represents 0% to 49% of the sum of x+y+z.
40. The method of forming a hybrid capacitor of claim 40, wherein x represents 70% to 90% of the sum of x+y+z, y represents 10% to 30% of the sum of x+y+z, and z represents 0% to 20% of the sum of x+y+z.
41. The method for forming a hybrid capacitor of claim 38 wherein the anionic counterion is polystyrene sulfonic acid.
42. The method for forming a hybrid capacitor of claim 23 wherein the homogenized dispersion further comprises a surfactant.
43. The method for forming a hybrid capacitor of claim 42, wherein the surfactant is selected from the group consisting of nonionic surfactants, fluorinated surfactants, anionic surfactants, cationic surfactants, and acetylenes.
44. The method of forming a hybrid capacitor of claim 23, wherein the liquid electrolyte comprises a solvent selected from the group consisting of gamma-butyrolactone, sulfolane, ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, acetonitrile, propionitrile, dimethylformamide, diethylformamide, water, silicone oil, polyethylene glycol, and mixtures thereof.
45. The method of forming a hybrid capacitor of claim 23, wherein the liquid electrolyte comprises a salt selected from the group consisting of inorganic acid ammonium salts, inorganic acid amine salts, inorganic acid alkyl substituted amide salts, organic ammonium salts, organic acid amide salts, organic acid alkyl and substituted amide salts.
46. A hybrid capacitor comprising: A sealed housing, comprising: an anode having a dielectric thereon; a conductive polymer layer on the dielectric, wherein the conductive polymer layer has a surface layer sulfur concentration of at least 1 wt %; Diaphragm; and Liquid electrolyte.
47. The hybrid capacitor of claim 46, wherein the surface layer sulfur concentration is at least 1.2 wt%.
48. The hybrid capacitor of claim 47, wherein the surface layer sulfur concentration is at least 1.4 wt%.
49. The hybrid capacitor of claim 46, wherein the anode comprises a metal or a metal oxide.
50. The hybrid capacitor of claim 49, wherein the metal or metal oxide comprises a valve metal.
51. The hybrid capacitor of claim 50, wherein the valve metal is selected from the group consisting of tantalum, aluminum, niobium, titanium, zirconium, hafnium, alloys of these elements, and conductive oxides thereof.
52. The hybrid capacitor of claim 51, wherein the valve metal is aluminum.
53. The hybrid capacitor of claim 46, wherein the conductive polymer layer comprises a conductive polymer defined by Formula A: in: X is selected from S, N or O; R 1 and R 2 independently represent a straight or branched C1-C16 alkyl or C2-C18 alkoxyalkyl group; or unsubstituted or substituted by C1-C6 alkyl, C1-C6 alkoxy, halogen or OR 3 Substituted C3-C8 cycloalkyl, phenyl or benzyl; or R 1 and R 2 together are unsubstituted or substituted straight chain C1-C6 alkylene groups: C1-C6 alkyl, C1-C6 alkoxy, halogen, C3-C8 cycloalkyl, phenyl, benzyl, C1-C4 alkylphenyl, C1-C4 alkoxyphenyl, halophenyl, C1-C4 alkylbenzyl, C1-C4 alkoxybenzyl or halobenzyl, R 1 and R 2 Together, they form a 5-, 6-, or 7-membered heterocyclic structure containing two oxygen elements. 3 Preferably it represents hydrogen, straight-chain or branched C1-C16 alkyl or C2-C18 alkoxyalkyl, or C3-C8 cycloalkyl which is unsubstituted or substituted by C1-C6 alkyl, phenyl or benzyl.
54. The hybrid capacitor of claim 53, wherein X is S.
55. The hybrid capacitor of claim 53, wherein the conductive polymer is 3,4-polyethylenedioxythiophene.
56. The hybrid capacitor of claim 36, wherein the conductive polymer layer comprises anionic counterions, the anionic counterions being defined as: A x B y C z in: A is polystyrene sulfonic acid or polystyrene sulfonate; B and C each represent a polymerized unit substituted by a group selected from the following: -carboxyl; -C(O)OR 6 , where R 6 Selected from the following groups: an alkyl group of 1 to 20 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, phosphate, acrylate, anhydride; and -(CHR 7 CH2O) b -R 8 ,in: R 7 is selected from hydrogen or an alkyl group of 1 to 7 carbons; b is 1 to -CHR 7 The CH2O- groups provide integers of molecular weight up to 200,000; and R 8 selected from the group consisting of hydrogen; silane; phosphate; acrylate; an alkyl group of 1 to 9 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxyl, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; -C(O)-NHR 9 ,in: R 9 is hydrogen or an alkyl group of 1 to 20 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; -C6H4-R 10 ,in: R 10 Selected from: hydrogen or alkyl optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; Reactive groups, the reactive groups are selected from the group consisting of hydroxyl, carboxyl, amine, epoxy, silane, imide, amide, thiol, olefin, alkyne, phosphate, azide, acrylate, anhydride; and -(O(CHR 11 CH2O) d -R 12 ,in: R 11 is hydrogen or an alkyl group of 1 to 7 carbon atoms, preferably hydrogen or methyl; d is 1 to be sufficient for -CHR 11 The CH2O- group provides integers of molecular weight up to 200,000; R 12 selected from hydrogen, alkyl groups of 1 to 9 carbons optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; -C6H4-OR 13 ,in: R 13 Selected from: hydrogen or an alkyl group optionally substituted with a reactive group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, acrylate, phosphate and anhydride; Reactive groups, the reactive groups are selected from: epoxy, silane, olefin, alkyne, acrylate, phosphate; and -(CHR 14 CH2O) e -R 15 ,in: R 14 is hydrogen or an alkyl group of 1 to 7 carbons; e is 1 to -CHR 14 The CH2O- groups provide integers of molecular weight up to 200,000; and R 15 selected from hydrogen and alkyl groups of 1 to 9 carbons optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, acrylate, phosphate, and anhydride; and x, y and z are sufficient to form a polyanion having a molecular weight of at least 100 and not more than 500,000, wherein y / x is from 0.01 to 100; and z is from 0 to a ratio of z / x not exceeding 100.
57. The hybrid capacitor of claim 56, wherein x represents 50% to 99% of the sum of x+y+z, y represents 1% to 50% of the sum of x+y+z, and z represents 0% to 49% of the sum of x+y+z.
58. The hybrid capacitor of claim 56, wherein x represents 70% to 90% of the sum of x+y+z, y represents 10% to 30% of the sum of x+y+z, and z represents 0% to 20% of the sum of x+y+z.
59. The hybrid capacitor of claim 46, wherein the anionic counterion is polystyrene sulfonic acid.
60. The hybrid capacitor of claim 46, wherein the liquid electrolyte comprises a solvent selected from the group consisting of gamma-butyrolactone, sulfolane, ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, acetonitrile, propionitrile, dimethylformamide, diethylformamide, water, silicone oil, polyethylene glycol, and mixtures thereof.
61. The hybrid capacitor of claim 46, wherein the liquid electrolyte comprises a salt selected from the group consisting of inorganic acid ammonium salts, inorganic acid amine salts, inorganic acid alkyl substituted amide salts, organic ammonium salts, organic acid amide salts, organic acid alkyl and substituted amide salts.
62. A dispersion comprising a conductive polymer, a dispersant, a monomer for said conductive polymer, and a molar excess of anionic counterions per mole of said conductive polymer and monomer, wherein said dispersion is homogenized.
63. The dispersion of claim 62, wherein the weight ratio of the conductive polymer and monomer to the anionic counterion in the dispersion is from 1:1.5 to 1:
5.
64. The dispersion of claim 63, wherein the weight ratio of the conductive polymer and monomer to the anionic counterion in the dispersion is from 1:2 to 1:
3.
65. The dispersion of claim 62, wherein the weight ratio of the conductive polymer to the anionic counterion in the hybrid capacitor is from 1:1.5 to 1:
5.
66. The dispersion of claim 65, wherein the weight ratio of the conductive polymer to the anionic counterion in the hybrid capacitor is from 1:2 to 1:
3.
67. The dispersion of claim 62, wherein the monomer is defined by formula A, wherein n=1, and there are no bonds between adjacent units; and the conductive polymer is defined by formula A: in: X is selected from S, N or O; R 1 and R 2 independently represent a straight or branched C1-C16 alkyl or C2-C18 alkoxyalkyl group; or unsubstituted or substituted by C1-C6 alkyl, C1-C6 alkoxy, halogen or OR 3 Substituted C3-C8 cycloalkyl, phenyl or benzyl; or R 1 and R 2 together are unsubstituted or substituted straight chain C1-C6 alkylene groups: C1-C6 alkyl, C1-C6 alkoxy, halogen, C3-C8 cycloalkyl, phenyl, benzyl, C1-C4 alkylphenyl, C1-C4 alkoxyphenyl, halophenyl, C1-C4 alkylbenzyl, C1-C4 alkoxybenzyl or halobenzyl, R 1 and R 2 Together, they form a 5-, 6-, or 7-membered heterocyclic structure containing two oxygen elements. 3 Preferably it represents hydrogen, straight-chain or branched C1-C16 alkyl or C2-C18 alkoxyalkyl, or C3-C8 cycloalkyl which is unsubstituted or substituted by C1-C6 alkyl, phenyl or benzyl.
68. The dispersion of claim 67, wherein X is S.
69. The dispersion of claim 67, wherein the conductive polymer is 3,4-polyethylenedioxythiophene.
70. The dispersion of claim 67, wherein the monomer is 3,4-ethylenedioxythiophene.
71. The dispersion of claim 62, wherein the anionic counterion is defined as: A x B y C z in: A is polystyrene sulfonic acid or polystyrene sulfonate; B and C each represent a polymerized unit substituted by a group selected from the following: -carboxyl; -C(O)OR 6 , where R 6 Selected from the following groups: an alkyl group of 1 to 20 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, phosphate, acrylate, anhydride; and -(CHR 7 CH2O) b -R 8 ,in: R 7 is selected from hydrogen or an alkyl group of 1 to 7 carbons; b is 1 to -CHR 7 The CH2O- groups provide integers of molecular weight up to 200,000; and R 8 selected from the group consisting of hydrogen; silane; phosphate; acrylate; an alkyl group of 1 to 9 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxyl, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; -C(O)-NHR 9 ,in: R 9 is hydrogen or an alkyl group of 1 to 20 carbon atoms optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; -C6H4-R 10 ,in: R 10 Selected from: hydrogen or alkyl optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; Active groups, the active groups are selected from: hydroxyl, carboxyl, amine, epoxy, Silanes, imides, amides, thiols, olefins, alkynes, phosphates, azides, Acrylates, anhydrides; and -(O(CHR 11 CH2O) d -R 12 ,in: R 11 is hydrogen or an alkyl group of 1 to 7 carbon atoms, preferably hydrogen or methyl; d is 1 to be sufficient for -CHR 11 The CH2O- group provides integers of molecular weight up to 200,000; R 12 selected from hydrogen, alkyl groups of 1 to 9 carbons optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, and anhydride; -C6H4-OR 13 ,in: R 13 Selected from: hydrogen or an alkyl group optionally substituted with a reactive group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, acrylate, phosphate and anhydride; Reactive groups, the reactive groups are selected from: epoxy, silane, olefin, alkyne, acrylate, phosphate; and -(CHR 14 CH2O) e -R 15 ,in: R 14 is hydrogen or an alkyl group of 1 to 7 carbons; e is 1 to -CHR 14 The CH2O- groups provide integers of molecular weight up to 200,000; and R 15 selected from hydrogen and alkyl groups of 1 to 9 carbons optionally substituted with a functional group selected from the group consisting of hydroxy, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, azide, acrylate, phosphate, and anhydride; and x, y and z are sufficient to form a polyanion having a molecular weight of at least 100 and not more than 500,000, wherein y / x is from 0.01 to 100; and z is from 0 to a ratio of z / x not exceeding 100.
72. The dispersion of claim 71 wherein x represents 50% to 99% of the sum of x+y+z, y represents 1% to 50% of the sum of x+y+z, and z represents 0% to 49% of the sum of x+y+z.
73. The dispersion of claim 72, wherein x represents 70% to 90% of the sum of x+y+z, y represents 10% to 30% of the sum of x+y+z, and z represents 0% to 20% of the sum of x+y+z.
74. The dispersion of claim 62, wherein the anionic counterion is polystyrene sulfonic acid.
75. The dispersion of claim 62, wherein the homogenized dispersion further comprises a surfactant.
76. The dispersion of claim 75, wherein the surfactant is selected from the group consisting of nonionic surfactants, fluorosurfactants, anionic surfactants, cationic surfactants, and acetylenes.
77. The dispersion of claim 62, wherein said forming said capacitor further comprises adding a liquid electrolyte.
78. The dispersion of claim 77, wherein the liquid electrolyte comprises a solvent selected from the group consisting of gamma-butyrolactone, sulfolane, ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, acetonitrile, propionitrile, dimethylformamide, diethylformamide, water, silicone oil, polyethylene glycol, and mixtures thereof.
79. The dispersion of claim 77, wherein the liquid electrolyte comprises a salt selected from the group consisting of inorganic acid ammonium salts, inorganic acid amine salts, inorganic acid alkyl substituted amide salts, organic ammonium salts, organic acid amide salts, organic acid alkyl and substituted amide salts.